Cyclic injection to reduce hydraulic fracture surface roughness in glutenite reservoirs. (June 2021) - Nie, Yuanxun; Zhang, Guangqing; Wen, Jing; Li, Shiyuan; Zhou, Dawei
Abstract: In glutenite reservoirs, hydraulic fracture surfaces are always rough due to the presence of gravels. The fracture surface roughness significantly affects the proppant transport, settlement, and supporting effectiveness during and after hydraulic fracturing. To reduce the fracture surface roughness in fracturing glutenite reservoirs, the cyclic injection was proposed and verified with hydraulic fracturing experiments on glutenite samples. After fracturing in experiments, a laser scanning system was used to scan and extract the fracture surface 3D data, of which the fracture surfaces were characterized with 5 parameters. Experimental results showed that the cyclic injection reduced the fracture asperity height by 30–70%, the standard deviation of the normal fracture asperity height reduced by over 52%. Meanwhile, the cyclic injection increased the penetration ratio (the number of those penetrated by hydraulic fractures divided by the total number of gravels along the fracture path) by 20% for gravel size of 2−6 mm and 30% for gravel size of 6−25 mm . The mechanism of the cyclic injection reducing fracture surface roughness was summarized: (i) the gravels damage enhanced by cyclic loads makes them prone to fracture penetrating; (ii) cyclic compression weakens gravels and the cements holding them near the fracture, then the fracture surface deformation (shearing/slipping) is responsible to gravel detachment. In the end, the fracturing fluid friction affected by the fracture surface roughness was evaluated. This study is helpful for understanding and tailoring the fracturing design when the fracture surface roughness plays a critical role in the glutenite reservoir stimulation. Highlights: 3D-scanned fracture surface shows cyclic injection reduces surface roughness in glutenite fracturing. Both cyclic tension, compression and shearing contribute to reduction in surface roughness. Cyclic tension induced damage makes gravels prone to be penetrated near fracture tip. Cyclic compression weakens the cements holding gravels along the fracture, responsible to gravel detachment.